Pengaruh Kepemilikan Akta Kelahiran Dan Akta Perkawinan Terhadap Capaian Kepemilikan Dokumen Administrasi Kependudukan Kabupaten Sikka Tahun 2023 - Iselia Lopes (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Population administration in Indonesia involves managing various aspects such as birth, marriage, death and identity. These records ensure legal identity and facilitate access to public services. In Sikka district, there is a significant shortage of birth certificates and marriage certificates with 52.83% of the population not having birth certificates by 2023 and 46.40% of married couples not having marriage certificates. This Policy Paper aims to achieve birth certificate and marriage certificate registration coverage in Sikka District by 2024 and develop policy recommendations to improve coverage. A quantitative approach is used to analyze the percentage of birth certificate and marriage certificate processing in 2023. In-depth interviews with civil registration officers and residents to identify challenges and perceptions related to the registration process were also conducted. The results of the analysis show that there is a significant gap in the ownership of birth certificates and marriage certificates in various sub-districts in Sikka district with contributing factors including many people not realizing the importance and benefits of having these documents, remote areas facing difficulties accessing civil registration services, the cost of going to the civil registry office is high and traditional/customary practices over legal documentation. To address this, the policy recommendations are the Sikka Regent Decree on the ASANTT application follow-up work plan and establishing mobile registration units and increasing the number of registration offices in remote areas.